Food Security Policy in Indonesia: The Impact to Land Ownership and Farmers’ Welfare - Yusuf Saeful Zamil; Ida Nurlinda; An Nissa Ayu Mutia; Puja Anudiwanti (Administrative Law Departement Faculty of Law Universitas Sebelas Mare, 2025)
Events such as the war between Russia and Ukraine are just one of many examples causing food crises across the globe, possibly leading to widespread famine. Given such a necessity, each state should make food security its main priority for development. An ideal food security policy must show an impact on agrarian reform or agrarian justice, particularly meant for the welfare of small farmers. The agrarian reform may help to increase the welfare of the small farmers as a program that gives access to the control and ownership of agricultural lands. This paper studies on how far the effect of food policy against agrarian reform in Indonesia. The result of the research shows that the food security policy in Indonesia is not yet capable of increasing the welfare of small farmers. Facts show that food security policy in Indonesia prioritizes allotment over agricultural and farming lands for big companies. The approach is claimed to entrust the role of food security development to the big companies or sometimes landlords. Only a small amount of access is granted to small farmers in terms of ownership and control over such lands. In facing such conditions, the authors come with a concept to transfer the Directorate of Agrarian Management from the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency to the Ministry of Agriculture. This way, food security programs will have no choice but to have farmers’ welfare to be included as one of their main objectives. A single chain of command will ease the process of implementation, and it will help the Government to have a better focus on achieving its goals, either for food security or the farmers’ welfare.